INVESTIGATION OF POTENTIAL ETIOLOGICAL CONTRIBUTORS TO PATHOMORPHOLOGICAL ASPECTS OF RENAL DAMAGE IN COVID-19 PATIENTS: A CROSS-SECTIONAL STUDY. - Prashant Kumar; Akhilesh Kumar; Rahul Raj (Student's Journal of Health Research, 2023)
Background: The COVID-19 pandemic extends beyond respiratory issues. It impacts various organs, including the kidneys, leading to complications such as acute kidney injury. Objectives: This study aimed to examine the histological characteristics of kidney damage among individuals who succumbed to COVID-19 and to elucidate underlying factors contributing to renal pathology in individuals with COVID-19. Methods: Utilizing a cross-sectional design, data were extracted from the medical records of 301 patients at Darbhanga Medical College and Hospital in Bihar, India. The primary focus was on individuals concurrently afflicted with SARS-CoV-2 infection and various kidney conditions, encompassing acute kidney injury (AKI), chronic kidney disease (CKD), nephritic syndrome, nephrotic syndrome, etc. Diverse data elements, including demographics, clinical outcomes, treatment durations, diagnoses, and laboratory test results, were collected. Results: Key findings from this investigation revealed a positive correlation between elevated creatinine levels and older age, as well as an association between higher initial creatinine levels and shorter treatment duration. Notably, patients who did not survive exhibited significantly higher initial creatinine levels compared to discharged patients. Patients diagnosed with COVID-19 and AKI experienced an extended hospital stay compared to those without AKI. Moreover, individuals with AKI complicating CKD experienced a significantly extended hospitalization period compared to those without AKI. Importantly, individuals with AKI faced a substantially higher risk of mortality compared to subjects who were diagnosed with CKD only. Furthermore, individuals suffering from AKI had a considerably elevated risk of mortality when compared to individuals without CKD or AKI. Conclusion: This study highlights its impact on clinical outcomes, the importance of early creatinine measurement, and the risk associated with advanced age and AKI complications. Recommendation: Consider closely monitoring elderly individuals with COVID-19, as advanced age is identified as a significant risk factor for the development of AKI as a complication of CKD.